Climate change adaptation in Pacific countries : fostering resilience and improving the quality of life - Leal Filho, Walter (Springer, 2017)
This book showcases vital lessons learned from research, field projects and best practice examples with regard to climate change adaptation in countries throughout the Pacific region, a part of the planet that is particularly vulnerable to and affected by climate change. The book's primary goals are to document the wealth of experiences in the region available today, to encourage cross-sector interactions among the various stakeholders in the region, and to help transfer results to other countries and regions. Accordingly, it gathers a set of papers presented at a symposium on climate change adaptation held in Fiji in July 2016, focusing on "Fostering Resilience and Improving the Quality of Life". In these contributions, local and international experts present a variety of initiatives showing how Pacific countries are coping with the many problems associated with climate change, including initiatives in education and awareness work taking place across the region, operational aspects and their implications for policy-making, and challenges in urban and rural areas.
Keywords: Human beings -- Effect of climate on -- Pacific Area.; Climatic changes -- Pacific Area.; Pacific Area.; elektronické knihy; electronic books